2002
DOI: 10.1104/pp.003087
|View full text |Cite
|
Sign up to set email alerts
|

A Role for Diacylglycerol Acyltransferase during Leaf Senescence

Abstract: Lipid analysis of rosette leaves from Arabidopsis has revealed an accumulation of triacylglycerol (TAG) with advancing leaf senescence coincident with an increase in the abundance and size of plastoglobuli. The terminal step in the biosynthesis of TAG in Arabidopsis is catalyzed by diacylglycerol acyltransferase 1 (DGAT1; EC 2.3.1.20). When gel blots of RNA isolated from rosette leaves at various stages of development were probed with the Arabidopsis expressed sequence tag clone, E6B2T7, which has been annotat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
184
1
6

Year Published

2004
2004
2018
2018

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 216 publications
(202 citation statements)
references
References 62 publications
(60 reference statements)
11
184
1
6
Order By: Relevance
“…The implication of PG in the storage of catabolic molecules produced during senescence and nitrogen Planta (2013) 237:463-470 465 starvation has been described previously (Kaup et al 2002;Gaude et al 2007). However, the characterization of two PG acyl transferases has led to an advance in mechanistic understanding of the accumulation of fatty acid phytyl esters and triacylglycerols (Fig.…”
Section: Role Of Plastoglobules During Leaf Senescencementioning
confidence: 76%
See 3 more Smart Citations
“…The implication of PG in the storage of catabolic molecules produced during senescence and nitrogen Planta (2013) 237:463-470 465 starvation has been described previously (Kaup et al 2002;Gaude et al 2007). However, the characterization of two PG acyl transferases has led to an advance in mechanistic understanding of the accumulation of fatty acid phytyl esters and triacylglycerols (Fig.…”
Section: Role Of Plastoglobules During Leaf Senescencementioning
confidence: 76%
“…In contrary, the amount of TAGs in the mutant leaves is only 30 % lower, certainly due to the implication of other diacylglycerol acyltransferase enzymes such as DGAT1 (Zou et al 1999;Dahlqvist et al 2000;Lardizabal et al 2001;Kaup et al 2002). Moreover, in the updated and quantitative plastoglobule proteome study published recently by Lundquist and colleagues, in addition to PES1 and 2, a third esterase (At5g41120) was identified that may also participate in the synthesis of FAPEs and TAGs in plastoglobules (Lundquist et al 2012b).…”
Section: Role Of Plastoglobules During Leaf Senescencementioning
confidence: 99%
See 2 more Smart Citations
“…Second, diacylglycerol acyltransferase (DGAT) activity can result in an increase in TAG. The DGAT is responsible for the incorporation of FFA in mono-and digalactosyl glycerides resulting in TAG (Kaup et al, 2002;Lung and Weselake, 2006). The activity of DGAT has been reported before in silages Van Ranst et al, 2009a).…”
Section: Silagesmentioning
confidence: 85%